Rice endosperm and bran proteins ameliorate diabetic osteoporosis in Zucker Diabetic Fatty rats - Masatoshi Kubota; Shogo Sugaki; Erika Komori; Reiko Watanabe; Yuki Higuchi; Yukikazu Harada; Hiroyuki Hashimoto; Shinobu Fujimura; Motoni Kadowaki (Journal of Functional Foods)
We investigated whether rice protein ameliorates the osteoporosis associated with type 2 diabetes in Zucker diabetic fatty rats. Diets containing rice endosperm protein, rice bran protein, or casein were fed for 10 weeks. The rats exhibited an early stage of diabetic nephropathy and chronic kidney disease–mineral and bone disorder, and parameters reflecting mineral and bone metabolism and bone structure and strength were evaluated. Feeding casein to Zucker Diabetic Fatty rats increased their serum fibroblast growth factor 23 and parathyroid hormone concentrations, suggesting relative excess phosphorus intake, a low serum osteocalcin concentration, and a slightly elevated serum tartrate-resistant acid phosphatase-5b concentration, indicating bone catabolism. In addition, the microarchitecture and strength of the femur were impaired. However, feeding rice endosperm protein and rice bran protein improved these parameters to near normal. These results imply that feeding these rice proteins causes an amelioration of diabetic osteoporosis.